2020
DOI: 10.3390/ma13030675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthetic Fibers and Hydrated Lime in Porous Asphalt Mixture Using Multi-Criteria Decision-Making Techniques

Abstract: Porous asphalt is a type of mixture characterized by having high air void percentages that offers multiple benefits when used in wearing courses in terms of driving safety, water flow management, and noise reduction. However, the durability of porous asphalt (PA) mixtures is significantly shorter when compared to dense-graded asphalt mixtures. This study investigated the impact of polyolefin–aramid fibers and hydrated lime in the functional and mechanical performance of porous asphalt mixtures. A parametric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Additionally, Daniel et al [ 128 ] found that introducing 19 mm long polyolefin-aramid fibers into warm mix asphalt improved stiffness modulus by 89% and fatigue life by 100%. Slebi-Acevedo et al [ 129 ] concluded that the combination of a porous asphalt mix with 19 mm polyolefin-aramid fibers at a dosage of 0.05% by mix weight and hydrate lime enhanced the mechanical properties of the porous asphalt mix.…”
Section: Results and Analysismentioning
confidence: 99%
“…Additionally, Daniel et al [ 128 ] found that introducing 19 mm long polyolefin-aramid fibers into warm mix asphalt improved stiffness modulus by 89% and fatigue life by 100%. Slebi-Acevedo et al [ 129 ] concluded that the combination of a porous asphalt mix with 19 mm polyolefin-aramid fibers at a dosage of 0.05% by mix weight and hydrate lime enhanced the mechanical properties of the porous asphalt mix.…”
Section: Results and Analysismentioning
confidence: 99%
“…In order to detect a preference among all mixture designs, a preference ranking model was developed. The significant levels were detected 0.05% and 5.0% for fiber and binder content, respectively, for optimum response [34]. The aggregate particles selected from the quarries depending upon the petrographic properties.…”
Section: Introductionmentioning
confidence: 98%
“…Gupta et al [ 37 ] incorporated aramid and glass fibers into porous asphalt mixtures and concluded that the aramid fibers showed remarkable improvement in abrasion resistance. Slebi-Acevedo et al [ 38 ], conducted research on polyacrinite and polyolefin plus aramid fibers in porous asphalt mixtures. It was found that the use of polyolefin plus aramid fibers enhanced abrasion resistance, reduced binder drainage, and improved the toughness of porous asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%